ANALYSIS OF COHESION ERRORS IN ALEXANDER HERY'S SHARIA ACCOUNTING BOOKS WITH A FOCUS ON STUDYING THE USE OF INTERSENTENCE CONJUNCTIONS - N Tatat Hernawati; Ika Mustika (JLER (Journal of Language Education Research), 2022)
The number of errors in the use of conjunctions in writing academic books makes the authors interested in carrying out research related to the cohesion of a paragraph in academic books. The purpose of this research is to describe the cohesion errors that exist in Alexander Hery's Islamic Accounting book. The method used is a qualitative method with a descriptive approach. The data source of this research is Alexander Hery's Islamic Accounting book. The data of this research are sentences in paragraphs that contain cohesion errors. Data analysis was carried out using descriptive qualitative analysis techniques. The results of this study indicate that there is cohesion in the use of conjunctions between sentences twelve times in the Islamic Accounting book. Researchers found an error in the use of the word "yang" used at the beginning of the sentence as connecting conjunction between the first sentence to the next sentence which makes the sentence in the paragraph difficult to understand. The conclusion is that there are still errors in the use of conjunctions in the Islamic Accounting book by Alexander Hery.